PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. POS INDONESIA (Persero) DI KOTA MAKASSAR - Muhammad Carda P (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims: 1) to determine and analyze the influence of motivation on employee performance at PT. Pos Indonesia (Persero) in Makassar City, and 2) to know and analyze the influence of work environment on employee performance at PT. Pos Indonesia (Persero) in Makassar City. In this study used multiple regression analysis method. The research data used were obtained from interview, documentation and questionnaire. The results of this study indicate that: 1) the influence of motivation variables have a positive and significant impact on employee performance at PT. Pos Indonesia (Persero) in Makassar City. This means the higher the form of motivation given the higher the level of achievement, but also the employees who have high work motivation then they will have the impetus to want to use all the ability to work, and 2) the influence of work environment variables positively and significant to employee performance at PT. Pos Indonesia (Persero) in Makassar City. This shows that to manage human resources effectively, then one of the factors that must be considered the company is the work environment that can affect the formation of potential resources. A good working environment is a work environment that provides a sense of comfort for employees to perform work activities that ultimately affect the performance it achieves.